Evolutionary Considerations on the Emerging Subculture of the E-psychonauts and the Novel Psychoactive Substances: A Comeback to the Shamanism? - Orsolini, Laura; St John-Smith, Paul; McQueen, Daniel; Papanti, Duccio; Corkery, John; Schifano, Fabrizio (Current Neuropharmacology, 2017)
Background: Evolutionary research on drug abuse has hitherto been restricted to proximate studies, considering aetiology, mechanism, and ontogeny. However, in order to explain the recent emergency of a new behavioral pattern (e.g. ‘the e-psychonaut style’) of novel psychoactive substances’ (NPS) intake, a complementary evolutionary model may be needed. Objective: A range of evolutionary interpretations on the ‘psychonaut style’ and the recent emergency of NPS were here considered. Method: The PubMed database was searched in order to elicit evolutionary theory-based documents commenting on NPS/NPS users/e-psychonauts. Results: The traditional ‘shamanic style’ use of entheogens/plant-derived compounds may present with a range of similarities with the ‘e-psychonauts’ use of mostly of hallucinogen/psychedelic NPS. These users consider themselves as ‘new/technological’ shamans. Conclusion: Indeed, a range of evolutionary mechanisms, such as: optimal foraging, costly signaling, and reproduction at the expense of health may all cooperate to explain the recent spread and diffusion of the NPS market, and this may represent a reason of concern.
Keywords: shamanism